Handbook of critical and indigenous methodologies / editors, Norman K. Denzin, Yvonna S. Lincoln, Linda Tuhiwai Smith. - Denzin, Norman K.; Lincoln, Yvonna S.; Smith, Linda Tuhiwai, 1950- (SAGE, 2008)
A comprehensive body of work that represents the state of the art for critical methodologies and indigenous discourses, this book covers everything from the history of critical and indigenous theory and how it came to inform and impact qualitative research and indigenous peoples to the critical constructs themselves.